GEOECOLOGY OR LANDSCAPE ECOLOGY. WHAT ARE THESE: GEOGRAPHY'S SUCCESSES OR ITS CRISIS? - V. A. Shalnev; V. V. Melnichuk (Наука. Инновации. Технологии, 2022)
Introduction. n the mid-20th century, against the background of increasing contradictions and growing problems of interaction between society and nature, the concept of ecology receives a new status. From modest biological science, it is set as "a new philosophy" and "a new religion of modern human life." The main directions of her theory were based on the biosphere concept created by VI. Vernadsky in the early 20th century. The realities of modern geographical reality, including the teaching of geographical shell and landscapes, were hardly used in this approach. The notion of a geographical environment has also been lost. The term environment is common, which in geographical reality refers only to private phenomena. Materials and methods of the research. Methodological basis was the concept of geographical environment and geographical determinism. Results of the study and their discussion. In modern realities, the teaching of a geographical environment in which the natural component plays a leading role with the concept of geographical determinism should be the subject of "Geoecology." Its purpose is to control the quality and trends of transformation of the geographical environment as a whole (as a generic concept) and its separate species of spherical structures of the Earth (geological, physical and geographical abiotic, biosphere and landscape sphere environment). The environment is already the subject of a study by Landscape Ecology as part of Ecological Geography, which studies regional environmental issues. Such an environment is formed within natural, human-cultivated and cultural landscapes created by it in the process of subject-object and subject-subject relations in a particular place of life. It is the environment of a person's place of life during a short (most often daily) cycle of his life. It is complex and reflects all the variety of media that N.F. Reimers (1990) described. Conclusions. The complexity of the structure of modern geographical reality determines the great variety of environments of life of biota and man (mankind) in modern rapidly changing realities. The use of geospatial and activity approaches as the methodological basis of the concept of the geographical environment (generic concept) allows to consider the continuity of different kinds of spherical environments in the geographical shell in the hierarchical sequence of their formation.